Алгебраическая модель турбулентности для течений с повышенной степенью турбулентности внешнего потока - Капинос, Василий Максимович; Пустовалов, Владимир Николаевич; Иванченко, Е. Н. (НТУ "ХПИ", 2008)
Розглянуто систему рівнянь, що описують алгебраїчну модель турбулентності, яка враховує ступінь турбулентності зовнішнього потоку. Порівняння розрахункових величин інтегральних характеристик турбулентного прикордонного шару та їхніх значень по експериментальним даним підтверджують ефективність запропонованої моделі турбулентності.

The system of equations is considered which describes an algebraic turbulent model, which takes into account the free-stream turbulence level. Comparison of calculated and experimental values of integral characteristics of a turbulent boundary layer confirm effectiveness of the proposed model of turbulence.
Algebraic turbulent model for with the free-stream turbulence level
Keywords: ЭВМ; гидрогазодинамика; профиль Коулса; модель турбулентности Сбеси-Смита; профиль скорости; коэффициент трения